Best of Airline, Vol.1 - London Weekend Television, ltd.; Granada Films (Canada: VEI, 2005)
Captures the unforgettable and oh-so-familiar realities of flying. At the same time, the behind-the-scenes views of America's fourth largest carrier, Southwest Airlines, brings a new appreciation for ever landing at your correct destination.
Vol. 1: The customer is always right -- Under the influence -- Fogbound -- Don't forget your passport-- Better late than never --
DVD ; Dolby Digital.
Keywords: Southwest Airlines Co; Airlines; Aeronautics, Commercial; Airlines -- Management